Circular RNA (hsa_circ_0051240) promotes cell proliferation, migration and invasion in ovarian cancer through miR-637/KLK4 axis. Issue 1 (4th December 2019) - Zhang, Meiyin; Xia, Bairong; Xu, Ye; Zhang, Yongjian; Xu, Jin; Lou, Ge
Abstract: In this study, we identified hsa_circ_0051240 was significantly increased in ovarian cancer (OC) tissues. Our results indicated that silencing of hsa_circ_0051240 inhibited OC cell proliferation, migration and invasion in vitro, and also prevented OC tumour formation in vivo . In addition, the inhibitory effects by blockage of hsa_circ_0051240 could be attenuated by the miR-637 inhibitor. Furthermore, we also identified that hsa_circ_0051240 act as a sponge of miR-637, and miR-637 directly targeted KLK4 mRNA in OC cells. Altogether, hsa_circ_0051240 promotes OC cell proliferation, migration and invasion through inhibiting the miR-637/KLK4 axis. Therefore, these results demonstrated that the hsa_circ_0051240/miR-637/KLK4 axis might serve as a therapeutic target for OC treatment.